Revolusi Terapi MDR-TB: Kolaborasi Liquid Biopsy CFDNA, Pemetaan Genetik, dan CRISPR-RNAI Untuk Deteksi Dini dan Penanganan Presisi: A Literature Review - Rizka Fauziah (Jurnal Medika Hutama, 2025)
Multidrug-Resistant Tuberculosis (MDR-TB) is a global health issue with a high disease burden and limited therapeutic success rates. Limitations of conventional methods, such as bacterial culture and rapid molecular tests, include long examination duration, low sensitivity, and failure to detect minor infections that cause resistance. A literature review discusses a precision biomolecular approach through the integration of circulating free DNA (cfDNA)-based liquid biopsy, genetic mapping, and CRISPR-RNAi technology. Liquid biopsy may be able to detect Mycobacterium tuberculosis and resistance noninvasively, rapidly, and can be used for real-time therapy monitoring. Genetic mapping analysis is enhanced by the identification of specific mutations, which can then be targeted by the CRISPR-RNAi system. CRISPR-RNAi technology plays a role not only in highly sensitive diagnosis but also as a therapeutic strategy that inactivates resistance genes without disrupting the normal microbiota. The integration of these three approaches offers a new paradigm in MDR-TB management that is precise, personalized, and efficient, with the potential to shorten treatment duration, increase therapy effectiveness, and reduce the risk of further resistance.